SEDIMENTAÇÃO NO TALUDE CONTINENTAL DA FOZ DO AMAZONAS : estudo descritivo - SALIMOS PRAZERES, Thamires (2019)
This work aims to analyze the main characteristics of sediments from the continental slope of Foz do Amazonas. The Slope is represented by an accentuated topographic gradient, begun at the break of the platform. Two piston corer type samples were analyzed, collected at depths of 884 m and 1910 m. Being obtained data of granulometric parameters, organic matter, carbonate. The results showed sediments dominated by the silt fraction (87.6% in the R184 and 92.9% in the S122), with lower clay values (11.6% in the R184 and 4.1% in the S122) and sand (0.6% in the R184 and 2.9% in the S122). The carbonate values presented a mean of 6.7% in the R184, and 25.8% in the S122. Organic matter contents ranged from 0.8% to 7.7% in R184 and from 1.2% to 19.2% in S122. The sediments of both samples presented silt or silt classification according to the statistical parameters of the Shepard diagram (1954), and characteristics of high to very high hydrodynamic conditions according to the Perjrup (1988) diagram.